Tissue Doppler echocardiography – A case of right tool, wrong use - Thomas George (Cardiovascular Ultrasound, 2004)
Abstract Background The developments in echocardiography or ultrasound cardiography (UCG) have improved our clinical capabilities. However, advanced hardware and software capabilities have resulted in UCG facilities of dubious clinical benefits. Is tissue Doppler echocardiography (TDE) is one such example? Presentation of the hypothesis TDE has been touted as advancement in the field of echocardiography. The striking play of colors, impressive waveforms and the seemingly accurate velocity values could be deceptive. TDE is a clear case of inappropriate use of technology. Testing the hypothesis To understand this, a comparison between flow Doppler and tissue Doppler is made. To make clinically meaningful velocity measurements with Doppler, we need prior knowledge of the line of motion. This is possible in blood flow but impossible in the complex myocardial motion. The qualitative comparison makes it evident that Doppler is best suited for flow studies. Implications of the hypothesis As of now TDE is going backwards using an indirect method when direct methods are better. The work on TDE at present is only debatable 'research and publication' material and do not translate into tangible clinical benefits. There are several advances like curved M-mode, strain rate imaging and tissue tracking in TDE. However these have been disappointing. This is due to the basic flaw in the application of the principles of Doppler. Doppler is best suited for flow studies and applying it to tissue motion is illogical. All data obtained by TDE is scientifically incorrect. This makes all the published papers on the subject flawed. Making diagnostic decisions based on this faulty application of technology would be unacceptable to the scientific cardiologist.